Civic Philosophy: Miguel Ángel Quintanilla (2020): Filosofía ciudadana. Ed. Trotta, Madrid. 193 pp. - Brugnami, Enrico (Analysis. Journal of Philosophical Research, 2021)
Review of: Miguel Ángel Quintanilla (2020): Filosofía ciudadana. Ed. Trotta, Madrid. 193 pp.